2022
DOI: 10.3390/ijerph19084744
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Addressing Occupational Stressors in Internet-Delivered Therapy for Public Safety Personnel: A Qualitative Analysis

Abstract: Internet-delivered cognitive behavioral therapy (ICBT) is effective when tailored to meet the needs of public safety personnel (PSP). Nevertheless, there is limited research on the nature of the occupational stressors faced by PSP who seek ICBT and how PSP use ICBT to address occupational stressors. We provided tailored ICBT to PSP (N = 126; 54% women) and conducted a qualitative content analysis on clinicians’ eligibility screening notes, clients’ emails, and clients’ survey responses to understand the occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…By addressing clients' previous suggestion of increasing contextual dimensions in the stories (e.g., parenting, neurodiversity), the stories may also become more realistic to clients. Some clients noted room for improvement on formatting, which has been previously reported ( Beahm et al, 2022 ), although current desires for the stories to be more concise or fewer in number is a new finding that has not been reported in previous evaluations of the Wellbeing Course.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…By addressing clients' previous suggestion of increasing contextual dimensions in the stories (e.g., parenting, neurodiversity), the stories may also become more realistic to clients. Some clients noted room for improvement on formatting, which has been previously reported ( Beahm et al, 2022 ), although current desires for the stories to be more concise or fewer in number is a new finding that has not been reported in previous evaluations of the Wellbeing Course.…”
Section: Discussionmentioning
confidence: 57%
“…Potential improvements included adding more examples that would assist PSP with the application of material to their circumstances ( Beahm et al, 2021 ). In a follow-up study, over one-third of clients from the same program reported that stories were helpful, with a small number (about 10 %) reporting not liking or not resonating with the stories ( Beahm et al, 2022 ). Some felt that the readability of written stories could be improved with font and colour changes or paired with audio and video narrations.…”
Section: Introductionmentioning
confidence: 99%
“…The current study results were also used to make iterative changes to PSPNET and supports the use of feedback from leaders as a method of improving ICBT. Previous PSPNET research has used data from clients to improve PSPNET courses but did not provide insights into outreach or promotion ( Beahm et al, 2022 ). Data from leaders in the current study provides complementary insights into facilitators, barriers, and improvements to outreach and promotion efforts.…”
Section: Discussionmentioning
confidence: 99%
“…In written feedback, PSP who participated in iCBT reported appreciating several aspects of iCBT, including the format and content, the accessibility of the course, the additional resources and examples, and the therapist guidance [ 12 ]. Nevertheless, some PSP also reported challenges with learning skills [ 13 ] and provided suggestions for improving iCBT, including adding more resources [ 12 ].…”
Section: Introductionmentioning
confidence: 99%